2020
DOI: 10.1155/2020/7051368
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of MEA + Water + CO2 Mixtures in Postcombustion CO2 Capture: A Review of Correlations and Experimental Studies

Abstract: The knowledge of physicochemical properties of a mixture of amine, water, and CO2 is beneficial in evaluating the postcombustion CO2 capture process and process equipment design. This study reviews the literature of density, viscosity, and surface tension measurements with the evaluated measurement uncertainties and proposed correlations for monoethanol amine (MEA), water, and CO2 mixtures. Adequate research has been performed to measure and develop correlations for pure MEA and aqueous MEA mixtures, but furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The post-combustion CO 2 capture is dominated by amine-based absorption, using aqueous solutions of mono-, di-, tri-ethanolamine or hindered amines to absorb CO 2 in gas form [232,278,[280][281][282][283]. Aqueous solutions are often used in order to control the density, viscosity, surface tension, and the thermal expansion coefficient of the pure amines [284][285][286]. This is while.…”
Section: Absorption (Wet Scrubbing)mentioning
confidence: 99%
See 1 more Smart Citation
“…The post-combustion CO 2 capture is dominated by amine-based absorption, using aqueous solutions of mono-, di-, tri-ethanolamine or hindered amines to absorb CO 2 in gas form [232,278,[280][281][282][283]. Aqueous solutions are often used in order to control the density, viscosity, surface tension, and the thermal expansion coefficient of the pure amines [284][285][286]. This is while.…”
Section: Absorption (Wet Scrubbing)mentioning
confidence: 99%
“…However, such high concentrations also increase the degradation rate, viscosity and the involved environmental concerns, posing challenges on the overall capture process [285,287]. In addition to aqueous solutions, both non-and low-aqueous solvents (i.e, water-lean solvent) are viable [284,288,289].…”
Section: Absorption (Wet Scrubbing)mentioning
confidence: 99%
“…The volume of the mixture ( V m ) deviates from the sum of volumes of pure components. Therefore, the excess molar volume ( V m E ) is a common approach to adjust the deviation from the ideal mixing caused by the difference in shape, size of components, and physical and chemical interactions among the component molecules as in eq . Moreover, the hydrogen bonding between molecules is also included in the intermolecular interactions, which makes the volume of the mixture deviate from the sum of partial molar volumes of pure components. where x i and V i are the mole fraction and the partial volume of a pure component i in a mixture, respectively.…”
Section: Density and Viscosity Modelsmentioning
confidence: 99%
“…Many researchers have reported empirical models of viscosity and density for common absorbents with CO 2 -unloaded or/and CO 2 -loaded solutions such as monoethanolamine (MEA), N -methyldiethanolamine (MDEA), diethanolamine (DEA), etc. Pinto et al suggested the NRTL-DVIS (for viscosity) and NRTL-DVOL (for density) models for amine solutions. They modeled viscosity and density using nonrandom two-liquid (NRTL)-based models. The NRTL-DVIS model was used to calculate the viscosity of multicomponent liquid mixtures of amine (ternary systems of H 2 O/MEA/MDEA, H 2 O/MEA/2-amino-2-methyl-1-propanol (AMP), and H 2 O/MDEA/DEA) .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in these properties will affect the mass transfer at the bottom of the absorber and the reaction kinetics in the stripper, thereby increasing the energy demand of CCS. Therefore, it is necessary to measure the physical properties during the absorption and desorption 25–30 . From the extensive literature survey, it was noted that the regeneration study of solvents is less reported, especially for blended solvent composed of MEA and IL.…”
Section: Introductionmentioning
confidence: 99%